LABORATORY MARKERS OF LIVER DISEASES IN CHILDREN: FROM DIAGNOSIS TO TREATMENT MONITORING (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Liver diseases in children can range from mild, self-limiting conditions to severe, life-threatening disorders. Early detection and accurate diagnosis are essential for effective management. Clinical laboratory diagnostics play a crucial role in identifying liver dysfunction and monitoring the progression of liver diseases. This article reviews common laboratory markers used in pediatric hepatology, including liver enzymes (ALT, AST), bilirubin, albumin, and prothrombin time, and their significance in diagnosing various hepatic conditions such as viral hepatitis, biliary atresia, and cirrhosis. The article also discusses the role of these markers in monitoring treatment response and disease progression.